2020
DOI: 10.1182/blood.2020005496
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic quantitation and causal analysis reveal pathways in GPVI/ITAM-mediated platelet activation programs

Abstract: Platelets engage cues of pending vascular injury through coordinated adhesion, secretion and aggregation responses. These rapid, progressive changes in platelet form and function are orchestrated downstream of specific receptors on the platelet cell surface, and through intracellular signaling mechanisms that remain systematically undefined. This study brings together cell physiological and phosphoproteomics methods incorporating peptide tandem mass tag (TMT) labeling, sample multiplexing, synchronous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 79 publications
1
46
0
Order By: Relevance
“…However, their targeted pathways need to be understood and assessed with valid assays. Such emerging strategies 65,98,99 are promising for the individualized screening of platelet-related diseases and drugs. Human platelets can serve here as prominent cellular model, but also as therapeutic and diagnostic target.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…However, their targeted pathways need to be understood and assessed with valid assays. Such emerging strategies 65,98,99 are promising for the individualized screening of platelet-related diseases and drugs. Human platelets can serve here as prominent cellular model, but also as therapeutic and diagnostic target.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Phosphoproteomics-based studies have identified JAK2 tyrosine phosphorylation downstream of both GPVI and CLEC-2. 44,45 In addition, Mpl/JAK2 signaling may also contribute to the regulation of platelet hemostatic function in vivo, as TPO potentiates GPVI signaling through a phosphatidylinositol 3-kinase-dependent pathway in human platelets. 46,47 Potentiation of platelet GPVI signaling by TPO is lost in platelets of JAK2 V617F patients.…”
Section: Discussionmentioning
confidence: 99%
“…A PV system of this scale could support 30% of annual and about 67% of daylight electricity needs in the city (Byrne et al, 2015). Closer evaluation of the Gangnam district in Seoul finds that the area could be home to almost 5 million m 2 of suitable rooftop space across its 27,000 buildings (Hong et al, 2017;Lee, Hong, Jeong, et al, 2018a;Lee, Hong, Jeong, et al, 2018b). An evaluation of 710 projects of the Korean Local Energy Savings Program (2012Program ( -2014 likewise found that cities in Korea could expect energy savings ranging from 18 to 45% with an average 30.5% savings through cost-effective implementation of various energy efficiency interventions (Yoon et al, 2017).…”
Section: Transformation Of the Urban Energy Metabolism In Korean Citiesmentioning
confidence: 99%